2013
DOI: 10.1038/modpathol.2012.228
|View full text |Cite
|
Sign up to set email alerts
|

HER2 in gastric cancer: a digital image analysis in pre-neoplastic, primary and metastatic lesions

Abstract: The assessment of human epidermal growth factor receptor 2 (HER2) status in gastric cancer is crucial in selecting patients who may benefit from targeted therapy, yet heterogeneous expression could represent an important drawback for HER2 testing. We aimed to analyze (i) HER2 heterogeneity in primary gastric cancers, pre-neoplastic and metastatic lesions and (ii) HER2 prognostic role. We studied 292 surgically resected primary gastric carcinomas and constructed 21 tissue microarrays including tumor tissue core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 68 publications
1
62
0
Order By: Relevance
“…[34][35][36] HER2 status has been reported to be associated with gastric cancer, and HER2 overexpression has been shown to be correlated with decreased overall survival. [37][38][39] Therefore, expression of Rb and HER2 were used in the present study as negative and positive markers, respectively, of neoplastic transformation. …”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] HER2 status has been reported to be associated with gastric cancer, and HER2 overexpression has been shown to be correlated with decreased overall survival. [37][38][39] Therefore, expression of Rb and HER2 were used in the present study as negative and positive markers, respectively, of neoplastic transformation. …”
Section: Introductionmentioning
confidence: 99%
“…Compared with excision specimens, the biopsy specimens may overestimate or underestimate HER2 status, and discrepancies may occur not only at the IHC level but also at the FISH level. Discordant HER2 results for paired specimens have been also reported for primary and metastatic carcinoma [25][26][27].…”
Section: Discussionmentioning
confidence: 89%
“…In the current study, discordant paired specimens represented nearly one-third of HER2-positive specimens (either biopsy or excision). HER2 testing of all available specimens is also advocated by other investigators [14,20,26,27]. Until future research determines the survival outcomes of patients with HER2 positivity in biopsy or excision specimens, the above strategy should be used in clinical practice if feasible.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the tumor invasive front at the primary sites in resected specimens, as it was previously reported that HER2 staining exhibits no preferential distribution within the tumor, with negligible variation between the tumor mucosal surface and the invasive front (24) and the tumor invasive front is closely involved in the metastatic process. However, Fusco et al (25) reported that there is discordance in the HER2 status between the tumor invasive front and other lesions and gastric cancer is known to exhibit heterogeneous HER2 expression (14,18). Therefore we examined all the sites of the primary tumor in the discordant case to determine whether there was heterogeneity of HER2 expression, in order to assess the discordance between primary and paired metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%